EXTH-55. REPURPOSING THERAPEUTICS IN PATIENT-DERIVED GLIOMAS AND AN IDH1 MUTANT GLIOMA MODEL - Schmidt, Christin (Neuro Oncol, 2017)
Malignant glioma is the most common primary brain tumor in adults, where ~70% of newly diagnosed cases represent glioblastoma. As a result, development of novel therapies has focused on this tumor rather than lower-grade gliomas. Mutations of isocitrate dehydrogenase (IDH) genes have been found in ~10% of glioblastomas and ~80% of grade II-III gliomas. Lack of pre-clinical animal models and patient-derived glioma cultures has prevented development of therapies targeting IDH mutant gliomas. Furthermore, IDH1 mutation is emerging as a poor therapeutic target. Instead of targeting highly expressed/amplified targets in glioma, hypermethylation resulting in down-regulation of proteins in IDH1 mutant glioma cells provides a unique opportunity to identify targets that are suppressed, and when inhibited, will sensitize tumors to therapies. To identify novel therapeutics targeting IDH1 mutant glioma cells, we have used the RCAS-Tva system to generate a pre-clinical glioma mouse model and patient-derived cultures displaying IDH1 mutation. We confirmed previous reports demonstrating that IDH1 mutant cells were sensitized to ionizing radiation and showed reduced DNA repair response compared to IDH1 wild-type cells. To repurpose existing therapeutics, we performed high-throughput screening of 2,177 approved compounds in IDH1 wild-type and mutant glioma cultures. We identified families of compounds that showed specificity in reducing cell viability of IDH1 mutant glioma cells, including topoisomerase, HDAC, ATM, BCL2, HSP90, and PI3K/mTOR inhibitors. In contrast, IDH1 wild-type glioma cells showed sensitivity to diverse families of compounds, including those targeting growth factor signaling pathways, PLK1, and HMG-CoA reductase. Identified candidate compounds are currently being validated in vitro and in pre-clinical glioma models. In conclusion, we have identified a number of approved compounds that can quickly be translated from bench to bedside to improve outcome for patients diagnosed with IDH mutant gliomas.